2008
DOI: 10.1021/jp7109093
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of Sulfur Dioxide in Some Room-Temperature Ionic Liquids

Abstract: The mechanism of sulfur dioxide reduction at a platinum microelectrode was investigated by cyclic voltammetry in several room-temperature ionic liquids (RTILs) , the peak appears at -1.0 V, and potential step chronoamperometry was used to determine that SO 2 has a very high solubility of 3100 ( (450) (2) kJ mol -1 using chronoamperometric data at different temperatures. The stabilizing interaction of the solvent with the reduced species SO 2 -• leads to a different mechanism than that observed in conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 44 publications
3
54
1
Order By: Relevance
“…110 The Stokes–Einstein relationship applies well in ILs in situations where the size of the diffusing species is close to that of the solvent molecules,111 provided that their diffusion corresponds reasonably well to the model which is based on macroscopic spheres moving through an incompressible medium. Thus, in cases like sulphur dioxide,104 hydrogen,112 and oxygen113 where there is a large size difference between the solute and the RTIL solvent ionic constituents, the inverse correlation between D and η predicted by Equation (17) is not observed. However, in general, the Stokes–Einstein equation provides an accurate description of the relationship between diffusion and viscosity in RTILs as has been demonstrated in the cases of self‐diffusion of some ionic liquids,114 and diffusion of cobaltocene, the colbaltocenium cation, ferrocene, the ferrocenium cation,52 and N,N,N′,N′ ‐tetramethyl‐ para ‐phenylenediamine (TMPD),115, 116 Figure 17 provides an example of the SO 2 system that deviates from Equation (17) and the ferrocene one that conforms to this Stokes–Einstein relationship.…”
Section: Dynamic Electrochemical Studies In Ionic Liquidsmentioning
confidence: 96%
See 1 more Smart Citation
“…110 The Stokes–Einstein relationship applies well in ILs in situations where the size of the diffusing species is close to that of the solvent molecules,111 provided that their diffusion corresponds reasonably well to the model which is based on macroscopic spheres moving through an incompressible medium. Thus, in cases like sulphur dioxide,104 hydrogen,112 and oxygen113 where there is a large size difference between the solute and the RTIL solvent ionic constituents, the inverse correlation between D and η predicted by Equation (17) is not observed. However, in general, the Stokes–Einstein equation provides an accurate description of the relationship between diffusion and viscosity in RTILs as has been demonstrated in the cases of self‐diffusion of some ionic liquids,114 and diffusion of cobaltocene, the colbaltocenium cation, ferrocene, the ferrocenium cation,52 and N,N,N′,N′ ‐tetramethyl‐ para ‐phenylenediamine (TMPD),115, 116 Figure 17 provides an example of the SO 2 system that deviates from Equation (17) and the ferrocene one that conforms to this Stokes–Einstein relationship.…”
Section: Dynamic Electrochemical Studies In Ionic Liquidsmentioning
confidence: 96%
“…Given the combination of cost incentive and need to remove impurities and take advantage of the use of a microelectrode, Compton et al 64. 73, 77, 104106 have designed a small volume electrochemical cell for use in RTILs that can be coupled to a vacuum line. One design is shown in schematic form in Figure 12.…”
Section: Experimental Aspects Of Voltammetry In Ionic Liquidsmentioning
confidence: 99%
“…Barrosse-Antle et al, while carrying out electroreduction of SO 2 in ionic liquids, showed that high concentrations of SO 2 could be achieved in a range of imidazolium ILs. 12 In forming the oxazolines, the IL may facilitate the quick removal of SO 2 from the reaction pathway due to its high affinity for SO 2 . Xylene at room temperature can only achieve SO 2 concentrations of 0.3 mol % and therefore is unable to facilitate removal of SO 2 from the product in the same way as the IL unless heated.…”
Section: Resultsmentioning
confidence: 99%
“…A saturated calomel electrode (SCE, KCl) was used as the reference electrode and a platinum wire was used as the auxiliary electrode. The electrochemical experiments were performed in homemade gas cell detailed in literature [24]. Field emission scanning electron microscope (FE-SEM) images were obtained on a JSM-600 field emission scanning electron microanalyser (JEOL, Japan).…”
Section: Reagents and Equipmentmentioning
confidence: 99%